Why We Swab: A library of stories in stem cell donation. Issue 10 (5th September 2022) - Jagelaviciute, Gabriele; Kum, Elena; Li, Edward W.; Rosenfeld, Aaron; Williams, Kenneth; Kandel, Rana; DeGurse, Natalie; Park, Brady; Okonofua, Sylvia; Sano, Lauren; Gerofsky, Moriah; Sharp, Alexander; et al.
Abstract: Background: Stories are powerful in their ability to disseminate information in a meaningful way. We hypothesized that a stem cell donation story library optimized for social media could support the education and recruitment of committed unrelated hematopoietic stem cell donors from needed demographic groups. Study Design and Methods: We developed Why We Swab, a library of stories on stem cell donation (facebook.com/WhyWeSwab ; instagram.com/WhyWeSwab ; twitter.com/WhyWeSwab ), and evaluated its impact across social and traditional media as well as on eligible potential donors' knowledge and attitudes towards donation. Results: As of December 2021, the library included 28 story arcs featuring 45 storytellers from diverse ancestral backgrounds, including 8 donor‐recipient stories. Overall, the stories reached >92, 000 people across social media. Notably, stories were republished by 18 print/ broadcast media outlets in Canada and by major medical organizations. A series of stories shown to 33 eligible potential donors improved mean total scores on a donation knowledge test (64% to 85%, p < 0.001), reduced mean ambivalence scale scores (3.85 to 2.70, p < 0.001), and improved participants' willingness to register as donors (45% to 73%, p < 0.005). Data are also shown demonstrating that stakeholders valued the library and that its deployment was associated with improved donor recruitment outcomes in Canada. Conclusion: Why We Swab is accessible and relevant to a wide audience, including stem cell donor registries and recruitment organizations seeking to improve their recruitment efforts as well as to blood and organ & tissue donation organizations who can adapt the Why We Swab model to their audiences.